Vascular Access Profile in Maintenance Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2014)
Introduction. The aims of this study was to evaluate maintenance hemodialysis population in a tertiary care hospital based dialysis unit for vascular access (VA) types, to compare native arteriovenous fistula (AVF) and arteriovenous graft (AVG) survival, and to assess risk factors for access failure. Materials and Methods. A total of 182 patients on maintenance hemodialysis were evaluated and followed up in terms of VA type and VA outcomes. Results. Among 103 prevalent patients, 15.5% initiated dialysis with AVF. At the time of the study, 67.9% of the prevalent patients had an AVF and 29.1% had AVG. Of 79 incident patients, 64% were followed up for more than 3 months by nephrologists before initiation of dialysis. Among these patients, 13.6% were initiated with AVF. There were 25 primary failures and 50 secondary failure episodes. Of the 50 secondary failures, 15 were AVF failures and 31 AVG failures. Vascular access survival was significantly superior with AVF as compared with AVG (P = .03). With longer dialysis periods, failure rates were higher. Follow-up with nephrologists prior to initiation of dialysis had a major influence on VA. Conclusions. Arteriovenous fistula is the best VA for maintenance hemodialysis. However, when the vasculature is not ideal for AVF, AVG should be constructed. A small percentage of our patients had fistula at initiation of dialysis. This is mainly due to late nephrology referrals and also due to reluctance of patients to undergo surgical access placement when they are relatively asymptomatic.